Corporate strategies for Equitable Bank - Choa, Nikki C. T. (Animo Repository, 1999)
Equitable Banking Corporation (EBC) is the 8th largest private domestic bank in the Philippines today. Over the last three years, it has embarked on a transformation emerging with a new logo and new image. It has built a formidable line up of subsidiaries and affiliates that offer a diverse financial service portfolio. As the Bank propels forward, it has to turn its internal capabilities to shield itself from threats but at the same time seize opportunities to keel inertia of growth going. The banks future strategy would be a triad of expanding branch network, increasing operating efficiency and improving marketing effectiveness. The expansion of branch network enables the Bank to widen market reach and at the same time provide a channel for selling the banks services. Increasing operating efficiency is essential in lowering cost while improving marketing effectiveness will increase sales. The currency crisis that has plagued the region for more than a year now has left the nations economy in rubbles. GNP and GDP growth are next to nil. Investment is down, import is down, and employment of overseas contract workers is likewise down. Indeed, it paints a grim portrait. The macroenvironment seems to abound with threats but in a crisis, there is opportunity as well. The Banks highly liquid position enables them to acquire smaller banks, which are not big enough to weather the storm, which would customer base and increase the resources. At the heart of the organization is a core management team providing the leadership to steer the company to greater heights. To support the team, the bank has competent marketing officers to serve the distinct needs of each client. This is the main source of the Banks competitive advantage, personal banking. This competitive advantage will give the Bank the edge to pull ahead of competitors in the same strategic group. A strategy is effective only if it is successfully implemented. The organizational effectiveness was assessed using the 7-S framework. Pivotal in the implementation of the strategies is the shared values that the firm should have. Making everyone in the organization a marketing person and to provide a strong esprit de corps among people with diverse background will spell the success of the company. The future looks bright when one is prepared. Equitable Bank aims to be a top-tier bank by the turn of century and the people will work together to make this vision a reality.